e-Counseling Education Services (e-CES) Effect on Quality of Life Post-Stroke Patients During the Covid-19 Pandemic - M Sobirin Mohtar; Malisa Ariani (JENDELA NURSING JOURNAL, 2022)
Background: the COVID-19 pandemic has significantly reduced the quality of life for people who have a history of chronic disease, one of which is stroke. Along with the increasing number of post-stroke patients during this pandemic related to physical function and vitality, of course, it affects the inability of his capacity to check with health services. The implementation of education is directly hit by time constraints and the pandemic situation, therefore it is necessary to have individual counseling through e-Counseling.Purpose: to analyze the effect of e-Counseling Education Services (e-CES) on WHO Quality Of Life (WHOQOL) Post-Stroke Patients during the Covid-19 Pandemic.Methods: pre-experimental with pre-test post-test one group design. The population in this study were people with post-stroke disease who were in the Banjarmasin city area and were affected by the pandemic. The sampling technique in this study was accidental sampling. The stages are identifying several areas affected by the pandemic, socializing health counseling online, followed by e-CES intervention and seeing the impact on WHO Quality of Life. Paired t-test was used in analayzing the data.Results: the pretest score with a mean of 72.67 was obtained, while in the post-test there was an increase in the average value of 75.23 with each p-value = 0.027.Conclusion: there is an effect of e-Counseling Education Services (e-CES) on the WHO Quality of Life (WHOQOL) of post-stroke patients during the Covid-19 pandemic.